Strategi Pemberdayaan Orang Tua untuk Mendukung Pembelajaran Anak di RA Nurul Hidayah Trengguli Demak - Siti Aisyah Sholihah; Jannati, Eka Arvita; Fu'ad Arif Noor (Rumah Riset Publisher, 2025)
This study aims to identify parental empowerment strategies in supporting children's learning at Raudlatul Athfal (RA) Nurul Hidayah Trengguli Demak and to understand its impact on children's academic and social development. Parental involvement is a key factor in the success of early childhood education. This research employs a qualitative descriptive approach with data collected through in-depth interviews, direct observations, and documentation. The subjects of the study include parents, teachers, and the principal of the institution. The findings reveal that effective parental empowerment strategies include raising awareness, active participation in school activities, two-way communication between parents and teachers, and training in home education skills. These strategies have proven to enhance children's learning motivation, academic achievement, and social skills. These results emphasize the importance of sustained collaboration between families and educational institutions to create a conducive learning environment for young children.